INVESTIGASI VARIASI LEBAR HISTERESIS PADA CONTROLEER ON-OFF TERHADAP PENURUNAN RIPPLE MOTOR TRAKSI KERETA CEPAT - Nur Apriyana Putri; Moch. Rusli; Rini Nur Hasanah (Jurnal Mahasiswa TEUB, 2023)
The propulsion system for the fast train in this study uses a three-phase induction motor.The weakness of the induction motor lies in speed control.By using the direct torque control (DTC) method it can be overcome, but this method causes ripples in the output. Therefore, in the DTC method there is an on-of controller which will be set to suppress the ripple value. Setting is done on the value of the on-of switch contained in the flux and torque hysteresis controller to determine the ef ect of varying the hysteresis width on the on-of controller on decreasing ripple. In addition, the execution time is also added to the simulation series in order to determine the ef ect on the DTC method.The result of this study is that the ripple percentage value can be reduced by setting the flux hysteresis controller, which is from 18.238% to 6.330%. Then, with the settings on the torque hysteresis controller can also be reduced, which is from 6.330% to 6.231%. While the addition of execution time on the simulation, the ef ect is directly proportional to the ripple width of the output torque graph. Keywords: three phase induction motor, ripple, direct torque control (DTC), on-of controlle DAFTAR PUSTAKA[1] Maspriyanto, et al. (2010), “Pengaturan Kecepatan Motor Induksi 3θ Menggunakan Kontrol PI Berbasis Direct Torque Control”, hlm 1-2, Surabaya. [2] J. Siniaga, et al. (2021), “Kinerja Pengereman Motor Induksi Tiga Fasa”, Vol. 10, hlm 114- 119, Medan. [3] Nugroho, et al. (2021), “Sistem Pengendalian Kecepatan Motor Tiga Fasa Menggunakan Metode Direct Torque Control”, Vol. 10, hlm 81-90, Surabaya. [4] Koshy, Melvin. (2014), “Direct Torque Control Schemes for Induction Motor”, hlm 10-13, Trivandum. [5] Enache, et al. (2019), “Particular Dynamic States of Railway Traction Asynchronous Motors”, Bucharest, Romania. [6] Zulfatman, (2006), “Desain Pengendalian Kecepatan Motor Induksi 3 Phase Dengan PID Kontroler”, Vol. 1, hlm 144-154, Malang. [7] Rusli, et al. (2020), “Synthesis-Algorithm Of Bang-bang Controller With Delayed Feedback On Temperature Controller Systems”, IEEE. [8] Rahmani, et al. (2014), “Fuzzy Logic Controller and Cascade Inverter for Direct Torque Control of IM”, London. [9] Obed, et al. (2018), “Reduction of Ripple for Direct Torque Controlled Three Phase Induction Motor Based on A Predictive Control Technique”, Vol. 22, Iraq